2022
DOI: 10.1002/mpr.1937
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service areas in Switzerland

Abstract: Objectives: Small area analysis is a health services research technique that facilitates geographical comparison of services supply and utilization rates between health service areas (HSAs). HSAs are functionally relevant regions around medical facilities within which most residents undergo treatment. We aimed to identify HSAs for psychiatric outpatient care (HSA-PSY) in Switzerland. Methods:We used HSAr, a new and automated methodological approach, and comprehensive psychiatric service use data from insurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Low utilization rates were replicated in the present sample, even though Switzerland and in particular the catchment area described in this manuscript is known for a comprehensive health care system associated with a high density of inpatient and outpatient health care providers. 23 , 39 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low utilization rates were replicated in the present sample, even though Switzerland and in particular the catchment area described in this manuscript is known for a comprehensive health care system associated with a high density of inpatient and outpatient health care providers. 23 , 39 …”
Section: Discussionmentioning
confidence: 99%
“…21 , 22 The current discourse aiming to improve alignment and resource allocation in psychiatric and psychotherapeutic services in Switzerland, furthermore, highlights the relevance of gaining a better understanding of the utilization of mental health services. 23 , 24 …”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, it has also been observed that rates of hospital procedures and admissions relate more closely to the supply of services than to a community's need 24 . It has been surmised that harm could occur to those utilising excessive supply of services to those who do not need them by exposing them to risks without certain benefit 25 . Likewise, it has also been observed that with a country's increase in economic growth, there is a corresponding growth in reported mental health disorders and demand for mental health care 26 .…”
Section: Discussionmentioning
confidence: 99%
“…24 It has been surmised that harm could occur to those utilising excessive supply of services to those who do not need them by exposing them to risks without certain benefit. 25 Likewise, it has also been observed that with a country's increase in economic growth, there is a corresponding growth in reported mental health disorders and demand for mental health care. 26 This may be due to increased public awareness and support for mental health in more affluent countries, with an associated reduction in stigma allowing sufferers to seek help more readily.…”
Section: Psychiatric Workforce Numbers and Projected Rural Needsmentioning
confidence: 99%
“…Moreover, the Swiss Health Observatory reported that 1.9 involuntary admissions per 1,000 inhabitants were registered the same year [ 25 ], one of the highest rates in Europe [ 26 ]. Despite a proclaimed shift from hospital-based to more community-based mental healthcare, inpatient care remains at the core of Switzerland’s mental health system [ 27 ]. In this context, exploring patients’ experience of hospitalisation and their feeling of being coerced while inpatient seems of utmost relevance.…”
Section: Introductionmentioning
confidence: 99%